Centrality Statistics of Symptom Networks of Schizophrenia: A Systematic Review - Buchwald, Khan; Narayanan, Ajit; Siegert, RJ; Vignes, Matthieu; Arrowsmith, Kim; Sandham, Margaret (Cambridge University Press, 2024)
The network theory of psychological disorders posits that systems of symptoms cause, or are associated with, the expression of other symptoms. Substantial literature on symptom networks has been published to date, although no systematic review has been conducted exclusively on symptom networks of schizophrenia, schizoaffective disorder, and schizophreniform (people diagnosed with schizophrenia; PDS). This study aims to compare statistics of the symptom network publications on PDS in the last 21 years and identify congruences and discrepancies in the literature. More specifically, we will focus on centrality statistics. Thirty-two studies met the inclusion criteria. The results suggest that cognition, and social, and occupational functioning are central to the network of symptoms. Positive symptoms, particularly delusions were central among participants in many studies that did not include cognitive assessment. Nodes representing cognition were most central in those studies that did. Nodes representing negative symptoms were not as central as items measuring positive symptoms. Some studies that included measures of mood and affect found items or subscales measuring depression were central nodes in the networks. Cognition, and social, and occupational functioning appear to be core symptoms of schizophrenia as they are more central in the networks, compared to variables assessing positive symptoms. This seems consistent despite heterogeneity in the design of the studies.
Keywords: centrality statistics; cognition; functioning; network analysis; network theory; psychopathology network; schizoaffective; schizophrenia; schizophreniform; symptom networks; centrality statistics; cognition; functioning; network analysis; network theory; psychopathology network; schizoaffective; schizophrenia; schizophreniform; symptom networks; 1109 Neurosciences; 1117 Public Health and Health Services; 1701 Psychology; Psychiatry; 3202 Clinical sciences; 5202 Biological psychology; 5203 Clinical and health psychology